Comparative study of Modified Tension Band Wiring versus Tension Band Through Parallel CannulatedCancellous Screws in Patella Fractures - Shrestha, Praphulla; Chalise, Pralhad Kumar; Paudel, Sujan Raj (Birat Journal of Health Sciences, 2020)
Introduction: Open reduction and internal fixation is indicated in patients with displaced patella fracturesand loss of the extensor apparatus.Transverse fractures of the patella are commonly treated with modified tension band wire (MTBW). Loosening of the wires along with the implant construct and soft tissue irritation by the wires had already been reported. The newer technique, tension band wiring through cannulated cancellousscrews(TBWCCS) is soft tissue friendly and gives better stability. Objective: The objective of this study is to compare the outcome of treatment of patella fractures by modified tension band wiring with k wires and tension band wiring through parallel cannulated cancellous screws in terms of union rate, functional outcome and complication rate. Methodology: We performed acomparative study between the two procedures from September 2017 to January 2019 at Nepal Medical College Teaching Hospital. Total of 40 patients, 20 in each groupware enrolled in the study.Allthe patients were followed at regular intervals. Time taken for radiographic union was recorded. Variables of Modified Hospital for Special Surgery Knee Score (MHSSKS) were recorded and graded till the last follow-up at 24 weeks. Complications of each procedure were recorded.The data was analyzed using SPSS version 16. Results: All fractures united at 12.20±3.03 weeks in MTBWgroup and 11.20±2.78 weeks in TBWCCS group. Complication rate was significantly higher in MTBW group. In TBWCCS group, 90% patients had good to excellent MHSSKS score whilein MTBW group, 75% had good to excellent results at 24 weeks. Pain during walking was significantly better in TBWCCS group. Conclusion: On the basis of our study, tension band wiring through cannulated cancellousscrews is an effective method of treatment of patellar fractures.